Fluids and Creeping Faults: Insights From Local Earthquake Tomography of the Creeping Section of the North Anatolian Fault - Szrek, Joel; Jolivet, Romain; Schurr, Bernd; Becker, Dirk; Martínez-Garzón, Patricia; Jara, Jorge; Çakir, Ziyadin (Copernicus GmbH, 2026)
Aseismic slip plays a key role in earthquake dynamics, but we currently do not fully understand why some faults slide aseismically. Aseismic slip is largely influenced by the fault zone's frictional behaviour, by its material composition, the presence of fluids, the geometry of the fault, and the fault zone fabric. Recent research has focused on the material composition, and more specifically on the evolution of resistance to slip with slip speed for different types of rocks. Generally, faults with rate-weakening behavior tend to host earthquakes, while faults with rate-strengthening behavior accommodate stress through aseismic slip. However, even in rate-weakening materials, low effective normal stress, induced by high pore fluid pressure, makes it unlikely for a slip instability to reach the critical size needed to nucleate regular earthquakes. Hence, the presence of high pressure fluid within fault zones may explain the presence of shallow aseismic slip along faults. However, we lack direct evidence of the presence of fluids along various faults where aseismic slip has been identified.We use data from a dense network of seismometers along the North Anatolian Fault Zone SEISMENET1 to investigate spatial changes in seismic velocity along the section hosting aseismic slip. This section slips aseismically since at least 1944 and is the epicentral region of the last two large earthquakes that have struck the area, namely the 1944 M7.3 Bolu-Gerede and the 1943 M7.6 Tosia-Ladik earthquakes. Using local earthquake tomography, we test for a possible presence of fluids in the fault zone and a damage zone surrounding the epicentral region of the 1943 and 1944 earthquakes.Our network includes 5 broadband seismometers and 10 geophones deployed around the creeping section along a narrow swath paralleling the fault trace. In addition to data from these 15 temporary stations, seismic data from 5 permanent broadband stations were collected. The final dataset includes 24,756 P arrivals and 21,311 S arrivals from 2,272 earthquakes, with magnitudes ranging from Mw0 to Mw4. We use the simul2023 code2 to simultaneously determine the 3D structure of the shallow crust and relocate the earthquake hypocenters.We find kilometer-scale shallow high vp/vs anomalies (values in range of 1.8 up to 1.95), consistent with a damage asymmetry aligned with the observed rupture directions of historical earthquakes, indicating long-term preferred rupture directions along this segment of the NAF. Additionally, the creeping section of the North Anatolian Fault is shown to correspond to a 30-km-long zone of vp/vs above 1.8, consistent with the presence of high pore fluid pressure within the fault zone. The findings provide compelling evidence that fluid processes, rather than fault zone rheology alone, significantly influence aseismic slip behavior along the NAF. Together, these results suggest a dynamic interplay between structural damage, rupture history, and fluid migration in controlling fault zone mechanics, with implications for improving seismic hazard assessment in creeping fault segments. 1https://geofon.gfz.de/waveform/archive/network.php?ncode=1O year=20222https://doi.org/10.5281/zenodo.1069507